The Effect of Using Kahoot Learning Media on Increasing Students’ Learning Interest in Social Studies - Andriani, Sania; Mulyana, Eldi; Rohman, Slamet Nopharipaldi (Future Science, 2025)
This study investigates the effect of using Kahoot as an interactive digital learning medium on improving students’ learning interest in Social Studies at SMP Negeri 3 Tarogong Kidul. A quantitative approach with a quasi-experimental design was applied, involving an experimental class using Kahoot and a control class using PowerPoint, each consisting of 36 students. Data were collected through pretest–posttest and learning interest questionnaires. The descriptive results indicated an improvement in the experimental class, with mean scores increasing from 78,75 (pretest) to 93,61 (posttest), compared to the control class, which improved from 81,53 to 88,19. Furthermore, the experimental class achieved higher mean scores in both Kahoot usage (21,33) and learning interest (27,58) compared to the control class (19,64 and 25,14, respectively). The correlation coefficient (R) was 0,556, showing a moderately strong positive relationship between the use of Kahoot and students’ learning interest, while the coefficient of determination (R²) of 0,309 indicates that Kahoot contributed 30,9% to the improvement of students’ learning interest. The simple linear regression analysis produced a significance value of < 0,001 (< 0,05) and a t-value of 3,903 greater than the t-table value of 1,690, confirming a positive and significant effect of Kahoot on learning interest. These findings suggest that integrating Kahoot in Social Studies effectively increases students’ engagement, curiosity, and enthusiasm during the learning process.